마이크로데이터 공표를 위한 통계적 노출제어 방법론 고찰 - 박민정; Min-jeong Park; 김항준; Hang J. Kim (Ŭngyong tʻonggye yŏnʼgu, 2016)
학술 연구나 정책 입안 등을 위한 심층적 자료 활용의 확대는 동시에 개별 정보 노출에 대한 염려도 증가시킨다. 때문에 최근 이십여 년 간 통계적 노출제어(정보보호) 분야에서 많은 논문들이 발표되었다. 본 논문은 그러한 연구 내용들을 정리하여 국내 통계인들과 기관들에게 소개하고자 한다. 주요 내용으로 국소통합이나 잡음추가와 같은 전통적인 매스킹 기법 뿐만 아니라, 온라인 자료 분석 시스템에서의 정보보호 처리, 차등정보보호를 통한 노출제어 및 재현자료를 활용한 정보보호 대안 모색에 대해 다룬다. 또한 각각의 주제에 대한 방법론 소개와 함께 활용 사례 및 장단점을 논의하였다. 본 논문이 실제적인 통계적 노출제어 문제를 고민하는 통계인들에게 도움이 되기를 바란다. The increasing demand from researchers and policy makers for microdata has also increased related privacy and security concerns. During the past two decades, a large volume of literature on statistical disclosure control (SDC) has been published in international journals. This review paper introduces relatively recent SDC approaches to the communities of Korean statisticians and statistical agencies. In addition to the traditional masking techniques (such as microaggregation and noise addition), we introduce an online analytic system, differential privacy, and synthetic data. For each approach, the application example (with pros and cons, as well as methodology) is highlighted, so that the paper can assist statical agencies that seek a practical SDC approach.